Inflammatory markers as predictors of atrial fibrillation recurrence: Exploring the c-reactive protein to albumin ratio in cryoablation patients - KEPEZ, ALPER (My University, 2023)
BACKGROUND: Atrial fibrillation (AF) is a common cardiac rhythm disorder associated with hemodynamic disruptions and thromboembolic events. While antiarrhythmic drugs are often recommended as the initial treatment, catheter ablation has emerged as a viable alternative. However, the recurrence of AF following ablation remains a challenge, and there is growing interest in exploring inflammatory markers as predictors of recurrence. METHODS: This retrospective, cross-sectional analysis included 249 patients who underwent cryoablation for paroxysmal AF. The relationship between the ‘C-reactive protein (CRP) to albumin ratio (CAR)’ and AF recurrence was examined. RESULTS: Two hundred and forty-nine patients with paroxysmal non-valvular atrial fibrillation were included. They were divided into two groups: those without recurrence (Group 1) and those with recurrence (Group 2). Significant differences were observed in age (57.2 ± 9.9 vs. 62.5 ± 8.4, p = 0.001) and left atrial size (4.0 ± 0.5 vs. 4.2 ± 0.7, p = 0.001) between the two groups. In blood parameters, significant differences were found in CRP (5.2 ± 1.3 vs. 9.4 ± 2.8, p < 0.001) and neutrophil counts (5.1 ± 2.2 vs. 6.7 ± 3.6, p = 0.001). In univariate regression analysis, age (OR: 1.058, CI: 1.024–1.093, p = 0.001), WBC count (OR: 1.201, CI: 1.092–1.322, p < 0.001), neutrophil count (OR: 1.239, CI: 1.114–1.378, p = 0.001), CAR (OR: 1.409, CI: 1.183–1.678, p < 0.001), and left atrial diameter (OR: 0.968, CI: 0.948–0.989, p = 0.002) showed significant associations with AF recurrence. CONCLUSIONS: Inflammation plays a crucial role in the initiation and progression of AF. This study demonstrated that along with age, the CAR can serve as an independent predictor of AF recurrence following cryoablation.
Keywords: atrial fibrillation; C-reactive protein; CRP albumin ratio; cryoablation